PENGARUH IMPLEMENTASI SIA, KOMPETENSI SDM, DAN TEKNOLOGI INFORMASI TERHADAP LAPORAN KEUANGAN BERBASIS SAK EMKM - Haryanto, Dea Alverina; Triyanto, Eko (LPPM Institut Pendidikan Nusantara Global, 2024)
The research purposes were determined the effect of Accounting Information System, HR competency, and the use of information technology on the quality of financial reports based on SAK EMKM for MSME actors at Pusat Grosir Solo. The research applies quantitative survey research methods. The data collection method used a questionnaire. Research data includes primary. The data analysis used Multiple Linear Regression. The research results shown that 1) Accounting Information System implementation has no real effect on the quality of SAK EMKM-based financial reports for MSMEs at Pusat Grosir Solo. 2) The quality of human resources has a real influence on the quality of SAK EMKM-based financial reports for MSMEs at the Pusat Grosir Solo. 3) The use of information technology has a real influence on the quality of SAK EMKM-based financial reports for MSMEs at the Pusat Grosir Solo